PUTUSAN HAKIM BERDASARKAN IJTIHAD MENGENAI HUKUM KELUARGA ISLAM PADA MASA UMAR BIN KHATTAB - Azzahra, Lutfiah (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2023)
Umar bin Khattab was one of the caliphs who was famous for his firmness and tough temperament as well as being soft-hearted and intelligent. When he served as head of government or caliph, in what could be said to be quite a short time, Umar succeeded in bringing Islam to its glory days. This is proven by the large number of territories that were conquered by Muslims at that time. During his time, Islamic justice experienced rapid development where he succeeded in appointing judges who were competent in carrying out ijtihad and deciding cases, especially Islamic family matters. Apart from that, his policy is in regulating the principles and administration of justice, both relating to judges, the government, and litigants. In fact, this policy becomes a reference source in the judge's decision.